Intolerance of Uncertainty among Indonesian Workers During Covid-19 Pandemic - Afinnisa Rasyida; Maria Nugraheni Mardi Rahayu; Nindya Putri Aprodita (Universitas Ahmad Dahlan, 2022)
This research aims to describe the Intolerance of uncertainty (IU) among Indonesian workers during COVID-19 pandemic. A total of 351 workers in Java (64 males, 287 females) were involved as a participant. IU was measured using the Indonesian version of IUS-27. This study showed that most (41.9%) of the participants had a low level of IU; meanwhile, 36.8% of the participant had a high level of IU. The result of the difference test showed that there was a difference in IU between males and females (p=0.011) and between participants in the upper, middle, and lower SES (p=0.018). These findings show that females and people with low SES had a higher IU than other groups. These findings can be used as a reference by companies to identify and take preventive action toward workers who possessed a higher risk of developing a higher IU, especially in a situation full of uncertainty.Â